Candidate Species for Florida Aquaculture: Almaco Jack, Seriola rivoliana - Victor Blanco; Cortney Ohs; Nicole Rhody; Ronald Hans (EDIS)
Almaco jack, Seriola rivoliana, is a perciform within the order Perciformes, family Carangidae; which includes jacks and pompanos. They are members of the genus Seriola, a species of interest for aquaculture diversification worldwide. Like other commercially farmed Seriola species, almaco jack (also known as longfin yellowtail and kampachi) are fast growers, have a high market value, and are increasingly well-regarded among chefs for their versatility in both cooked and raw preparations. These characteristics, among others, have made them favorable candidates for both land-based and offshore aquaculture.